433 Gb silicosis cases following a recent guidance update. (24th April 2018) - Fishwick, David; Matthews, Sue; Kamil, Mohammed; Barber, Chris
Abstract : Introduction: Silicosis still occurs globally as a consequence of exposure to respirable crystalline silica (RCS). The Health and Safety Executive (HSE) regulates the workplace in Great Britain, and recently updated its silica based guidance relating to health surveillance. We report our early experience dealing with cases referred to our clinical service following this update. Methods: Our Occupational Lung Disease service runs a weekly multidisciplinary team (MDT) meeting. Following the relatively recent updated silica guidance issued by HSE, our clinical service offered to accept referrals of workers exposed to RCS who have undergone health surveillance at work. This would normally have consisted of lung function testing and a chest X Ray (CXR). A consultant respiratory physician and a radiologist, the latter reading to International Labour Organisation (ILO) radiology standards, discussed each case referred to the service at the MDT. Result: To date, 36 workers have been referred with potentially abnormal radiology. The mean age of this group of workers was 55 years (range 23–75), 8 were female. Twenty workers (56%), with a mean age of 55 years (range 35–75) and a mean duration of RCS exposure of 25.2 years (range 9–50), had an ILO grade recorded for the presence of small opacities on their CXR which were thought to be potentially consistent with silicosis. A further 11 were identified to have an incidental, not silica related, radiological abnormality and 5 had normal radiology. Discussion: Since HSE has refreshed and updated its silica based workplace guidance, workers have been identified with potentially abnormal chest x rays. Of those referred to us, a substantial proportion was identified to have small opacities consistent with silicosis. Workplaces must continue to risk assess all tasks potentially associated with RCS exposure, and subsequently intervene to reduce these exposures.